Cropland Bioaccumulation Risks of Potentially Toxic Elements in Soil of some Designated Foodstuffs Cultivated in Odu’a Farm Establishment, Aawe, Oyo State, Nigeria (Global Journal of Science Frontier Research, 2023)
The purpose of this work was to estimate heavy element bioaccumulation in four staple food crops species specifically sweet cassava Manihot esculenta maize Zea mays L plantain Musa paradisiaca L and white yam Dioscorea rotundata L and to assess the human health risks of food crops intake The analyzed heavy elements included arsenic cadmium copper manganese lead and zinc for their bioaccumulation factors to provide benchmark point information regarding ecological health and the suitableness of a farm established in the time ahead The bioaccumulation factor heavy elementpollution load index acceptable daily intake of elements human health risk index target hazard quotient toxicology total diet target hazard quotient and total target hazard quotienttechniques were employed to estimate the human health risks analysis caused by heavy elements via staple food crops consumption Quality control techniques comprised blank analysis spike recovery analysis and calibration of concentrations We adopted descriptive and inferential statistics to analyze the data Overall mean HEPLI values for both seasons were 0 54 and 0 88 0 28 and 0 92 0 31 and 0 37 0 52 and 0 55 0 28 and 0 55 and 0 24 and 0 31 for As Cd Cu Mn Pb and Zn respectively Elements in staple food crops were lower than in soils with ranges of 1 83- 3 91 0 02-0 06 0 06-0 43 10 30-26 14 0 04-0 23 and 2 73- 12 04 mg kg for As Cd Cu Mn Pb and Zn respectively The levels of heavy elements in consumable parts of the diverse staple food crops diminished in this order as plantain maize yam cassava Arsenic in the study staple food crops exceeded Food and Agriculture Organization World Health Organization guideline values Analysis of DAEs HHRI THQ TDTHQ and TTHQ for the four staple food crops indicated that local populations were unsafe and were at threat of potentially prolonged health effects from nutritional As
Keywords: toxic heavy elements; human health risk indices; staple food crops; farm establishment; ecosystem health